2011
DOI: 10.1017/s0022112011000152
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Kelvin–Helmholtz instability. Part 2. An experiment in fluids with a large viscosity contrast

Abstract: The stability of two-layer oscillatory flows was studied experimentally in a cylindrical container with a vertical axis. Two superposed immiscible liquids, differing greatly in viscosity, were set in relative oscillatory motion by alternating container rotation. Waves arising beyond a threshold were observed in detail for small oscillation frequencies ranging from 0.1 to 6 Hz. Measurements were performed on the growth rate and the wavenumber of these waves. The instability threshold was determined from the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
2
33
2
Order By: Relevance
“…It is worth highlighting that it is the first experimental evidence of spatially modulated waves on an interface caused by horizontal vibrations. Previous experimental studies of wave patterns under horizontal vibrations with immiscible fluids (Jalikop & Juel 2009;Yoshikawa & Wesfreid 2011b;Gandikota et al 2014b) did not report wave modulation, although it was theoretically predicted by Varas & Vega (2007) in a nearly inviscid fluid subjected to horizontal vibration. We will return to this pattern in § 4.3.…”
Section: Dynamics Of An Interface Near the Onset Of Instabilitymentioning
confidence: 92%
See 2 more Smart Citations
“…It is worth highlighting that it is the first experimental evidence of spatially modulated waves on an interface caused by horizontal vibrations. Previous experimental studies of wave patterns under horizontal vibrations with immiscible fluids (Jalikop & Juel 2009;Yoshikawa & Wesfreid 2011b;Gandikota et al 2014b) did not report wave modulation, although it was theoretically predicted by Varas & Vega (2007) in a nearly inviscid fluid subjected to horizontal vibration. We will return to this pattern in § 4.3.…”
Section: Dynamics Of An Interface Near the Onset Of Instabilitymentioning
confidence: 92%
“…The effect of horizontal vibrations on two superposed immiscible liquids has been examined both experimentally (Wolf 1969(Wolf , 1970Ivanova, Kozlov & Evesque 2001;Talib, Jalikop & Juel 2007;Mialdun et al 2008;Jalikop & Juel 2009;Yoshikawa & Wesfreid 2011b) and theoretically (Lyubimov & Cherepanov 1987;Khenner et al 1999), where it was shown that if the state of the flat contact line is unstable, nonpropagating periodic waves may occur on the interface. Following Wunenburger et al (1999), these waves, which are stationary in the reference frame of the vibrated cell, are referred to as 'frozen waves'.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found formation of waves perpendicular to the motion. In our experimental paper which is coupled with the present one (Yoshikawa & Wesfreid 2010), our setup utilized the same principle. Wolf (1969), Beysens et al (1998), Ivanova et al (2001a) and used the horizontal vibration of a fluid container to drive flows with a horizontal pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism is a parametric viscous instability in which the term 2 irkU in (14) resonates weakly damped modes described by (11). The mechanism is similar to the instability that causes surface waves in channel flow over a flat plat oscillating in its own plane [ Yih , ; Or , ; Gao and Lu , ], and is related to other parametric instabilities in viscous oscillatory flows [e.g., Yoshikawa and Wesfreid , ]. Instability in (14) requires that the squared Froude number true(ρ/ρtrue)2trueU2¯/(gh) exceed a threshold dependent on r/ω and the dimensionless wave number kgh/ω, with favored growth near kgh/ω=1, qualitatively consistent with the observations [ Traykovski et al ., ], for r/ω=O(1).…”
Section: Model Solutionsmentioning
confidence: 99%